UPAYA MEMBINA KELUARGA SAKINAH - Nur Puat (LPPM Institut Agama Islam Al-Hikmah Tuban, 2012)
Family sakinah, mawaddah, wa Rahmah, a family's dream is a goal even in a marriage. To shape it should start with a valid marriage according to Islamic law and regulations. The need for efforts to create sakinah families and their actions that should be avoided, which could result in rupture of marriage. Governments need to implement the family development programs in order to create a family as the purpose of marriage.